Knowledge About Dental Caries Using Dental Ludo Media (Grade 4 Students of MI Al Huda Kawedusan Ponggok Blitar) - Abidah, Azizah Belva; Larasati, Ratih; Marjianto, Agus (SURABAYA DENTAL THERAPIST JOURNAL, 2025)
According to the 2023 Indonesian Health Survey (SKI), the prevalence of caries among children aged 10-14 years is 63.8%. problem statement: findings from MI Al Huda Kawedusan Ponggok Blitar show a high prevalence rate of 83.3% suffering from dental caries, making the issue in this study the high incidence of dental caries among MI Al Huda Kawedusan Ponggok Blitar students in 2025. Method: This study is descriptive in nature, with 48 students as respondents. The research instrument used was a questionnaire sheet with multiple-choice questions to assess knowledge about dental caries. Results: The results indicate that the average knowledge of Grade 4 students at MI Al Huda Kawedusan Ponggok Blitar regarding the understanding, causes, effects, treatment, and prevention of dental caries was 43%, classified as insufficient, before using the Dental Ludo media. After using Dental Ludo, there was an increase in average knowledge among Grade 4 students at MI Al Huda Kawedusan Ponggok Blitar, with 95% of students having good knowledge about the understanding, causes, effects, treatment, and prevention of dental caries. Conclusion: In conclusion, the data collected and analyzed through the questionnaire show an improvement in the knowledge of Grade 4 students at MI Al Huda Kawedusan Ponggok Blitar regarding dental caries.